Should we worry about filter bubbles? - Frederik J. Zuiderveen Borgesius; Damian Trilling; Judith Möller; Balázs Bodó; Claes H. de Vreese; Natali Helberger (Internet Policy Review)
Some fear that personalised communication can lead to information cocoons or filter bubbles. For instance, a personalised news website could give more prominence to conservative or liberal media items, based on the (assumed) political interests of the user. As a result, users may encounter only a limited range of political ideas. We synthesise empirical research on the extent and effects of self-selected personalisation, where people actively choose which content they receive, and pre-selected personalisation, where algorithms personalise content for users without any deliberate user choice. We conclude that at present there is little empirical evidence that warrants any worries about filter bubbles.